2019
DOI: 10.1002/2211-5463.12685
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analysis of the callose enzyme families of fertile and sterile flower buds of the Chinese cabbage (Brassica rapa L. ssp. pekinensis)

Abstract: Callose is a β‐1,3‐glucan commonly found in higher plants that plays an important role in regulating plant pollen development. It is synthesized by glucan synthase‐like (GSL) and is degraded by the enzyme endo‐1,3‐β‐glucosidase. However, genome‐wide analyses of callose GSL and endo‐1,3‐β‐glucosidase enzymes in fertile and sterile flower buds of Chinese cabbage have not yet been reported. Here, we show that delayed callose degradation at the tetrad stage may be the main cause of microspore abortion in Chinese c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The protein sequence length of CalSs ranged from 1,494 to 1,979 amino acids, with an average MW of 212.88 kDa, and shared high similarity to the Arabidopsis thaliana CalS proteins ( Hong, Delauney & Verma, 2001 ). The isoelectric point (PI) values of the above genes were all greater than 7, indicating that CalSs in cotton were alkaline, which was the same as the biochemical properties of the CalSs in Chinese cabbage and Brassica ( Pu et al, 2019 ; Liu, Zou & Fernando, 2018 ). The CalSs were most likely localized in the plasma membrane, as predicted in Arabidopsis thaliana and Chinese cabbage ( Pu et al, 2019 ; Zavaliev et al, 2011 ).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The protein sequence length of CalSs ranged from 1,494 to 1,979 amino acids, with an average MW of 212.88 kDa, and shared high similarity to the Arabidopsis thaliana CalS proteins ( Hong, Delauney & Verma, 2001 ). The isoelectric point (PI) values of the above genes were all greater than 7, indicating that CalSs in cotton were alkaline, which was the same as the biochemical properties of the CalSs in Chinese cabbage and Brassica ( Pu et al, 2019 ; Liu, Zou & Fernando, 2018 ). The CalSs were most likely localized in the plasma membrane, as predicted in Arabidopsis thaliana and Chinese cabbage ( Pu et al, 2019 ; Zavaliev et al, 2011 ).…”
Section: Resultsmentioning
confidence: 91%
“…The isoelectric point (PI) values of the above genes were all greater than 7, indicating that CalSs in cotton were alkaline, which was the same as the biochemical properties of the CalSs in Chinese cabbage and Brassica ( Pu et al, 2019 ; Liu, Zou & Fernando, 2018 ). The CalSs were most likely localized in the plasma membrane, as predicted in Arabidopsis thaliana and Chinese cabbage ( Pu et al, 2019 ; Zavaliev et al, 2011 ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…GSL proteins have high molecular weight, containing 14–16 transmembrane domains grouped at the N‐terminal and C‐terminal regions, which leaves a central hydrophilic loop facing the cytoplasm (Chen & Kim, 2009; Schneider et al, 2016). The GSL genes have already been investigated in several species, such as grapevine (Yu et al, 2016), Citrus sinensis (Granato et al, 2019), Brassica rapa (Pu et al, 2019), Physcomitrella patens (Schuette et al, 2009), Zea mays (Niu et al, 2021), and Arabidopsis thaliana (Richmond & Somerville, 2000; Verma & Hong, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Callose synthase (CalS) is also referred to as glucan synthase-like (GLS; Richmond and Somerville, 2000 ; Verma and Hong, 2001 ). Twelve AtCalSs in Arabidopsis thaliana have been described ( Hong et al, 2001 ), as well as 12 CsCalSs in Citrus sinensis ( Granato et al, 2019 ), 32 BnCalSs in Brassica napus ( Liu et al, 2018 ), 8 VvCalSs in Vitis vinifera ( Yu et al, 2016 ), 7 HvCalSs in Hordeum vulgare ( Schober et al, 2009 ), 15 BraCalSs in Chinese cabbage ( Pu et al, 2019 ), and 27, 28, 16, and 15 GhCalSs, respectively, in Gossypium hirsutum , G. barbadense , G. raimondii , and G. arboreum ( Feng et al, 2021 ) have been reported.…”
Section: Introductionmentioning
confidence: 99%